Machine translations for translating metaphor - Artanti, Farahita Mufidah; Rahayu Purbasari (Lililacs Journal, 2024)
This study identifies and compares the translation procedures used by Google Translate, U- Dictionary, and Kamus Inggris (Kamusku) in translating metaphors found in Edgar Allan Poe’s short stories, namely Hop Frog, A Descent into The Maelstrom and The Fall of the House of Usher. The most common procedure used by all three translation tools is reproducing the same essence in the target language. Google Translate is the most varied in its approach, while Kamus Inggris frequently deletes metaphors. The study highlights the strengths and weaknesses of each tool in handling metaphor translation. Out of 40 metaphors, Google translate used the procedure for 21 times, U-Dictionary used it for 19 times, and Kamus Inggris (Kamusku) used it for 20 times. Lastly, translating metaphor as simile along with its sense is not used by the three machine translations.